Akkermansia muciniphila and its metabolite propionic acid maintains neuronal mitochondrial division and autophagy homeostasis during Alzheimer’s disease pathologic process via GPR41 and GPR43 - Zifan Wang; Cai Wang; Boyu Yuan; Li Liu; Haoming Zhang; Mingqiang Zhu; Hongxia Chai; Jie Peng; Yanhua Huang; Shuo Zhou; Juxiong Liu; Liyong Wu; et al. (Microbiome)
Abstract Background Alzheimer’s disease (AD) is a prevalent neurodegenerative disease (ND). In recent years, multiple clinical and animal studies have shown that mitochondrial dysfunction may be involved in the pathogenesis of AD. In addition, short-chain fatty acids (SCFA) produced by intestinal microbiota metabolism have been considered to be important factors affecting central nervous system (CNS) homeostasis. Among the main mediators of host-microbe interactions, volatile fatty acids play a crucial role. Nevertheless, the influence and pathways of microorganisms and their metabolites on Alzheimer’s disease (AD) remain uncertain. Results In this study, we present distinctions in blood and fecal SCFA levels and microbiota composition between healthy individuals and those diagnosed with AD. We found that AD patients showed a decrease in the abundance of Akkermansia muciniphila and a decrease in propionic acid both in fecal and in blood. In order to further reveal the effects and the mechanisms of propionic acid on AD prevention, we systematically explored the effects of propionic acid administration on AD model mice and cultured hippocampal neuronal cells. Results showed that oral propionate supplementation ameliorated cognitive impairment in AD mice. Propionate downregulated mitochondrial fission protein (DRP1) via G-protein coupled receptor 41 (GPR41) and enhanced PINK1/PARKIN-mediated mitophagy via G-protein coupled receptor 43 (GPR43) in AD pathophysiology which contribute to maintaining mitochondrial homeostasis both in vivo and in vitro. Administered A. muciniphila to AD mice before disease onset showed improved cognition, mitochondrial division and mitophagy in AD mice. Conclusions Taken together, our results demonstrate that A. muciniphila and its metabolite propionate protect against AD-like pathological events in AD mouse models by targeting mitochondrial homeostasis, making them promising therapeutic candidates for the prevention and treatment of AD. Video Abstract